2011
DOI: 10.3329/bsmmuj.v3i2.7056
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits of Substance Users in Bangladesh

Abstract: Abstract:Background: Drug taking behavior and drug dependence is a multi-factorial disorder. Personality is a very important determining factor of drug dependence. Objectives: To find out the possible relationship between personality traits and substance use disorders. Methods: This was a descriptive, cross-sectional and case-control study conducted in the department of Psychiatry of Bangabandhu Sheikh Mujib Medical University and Central Drug Addiction Treatment Center, Dhaka for a period of one year (January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
(9 reference statements)
0
5
1
Order By: Relevance
“…But low mean score on factor Q4 (tense) were seen among opioids user in our study reflecting that opioid users tend to be relaxed, composed and satisfied, (Not frustrated). But this finding was found to be contradicting with the results seen in the study conducted by Roy et al [4] The possible explanation might be people start taking opioids to overcome their anxiety issues, after that they start taking opioids to combat with their anxiety symptoms and to feel more relaxed and composed. Echeburuaet.al.…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…But low mean score on factor Q4 (tense) were seen among opioids user in our study reflecting that opioid users tend to be relaxed, composed and satisfied, (Not frustrated). But this finding was found to be contradicting with the results seen in the study conducted by Roy et al [4] The possible explanation might be people start taking opioids to overcome their anxiety issues, after that they start taking opioids to combat with their anxiety symptoms and to feel more relaxed and composed. Echeburuaet.al.…”
Section: Resultscontrasting
confidence: 69%
“…al. [4] where case controlled cross sectional study on 250 cases of substance use disorder and same number of control with similar socio demographic profile was taken up. The personality traits were measured using Eysenck personality questionnaire.…”
Section: Resultsmentioning
confidence: 99%
“…51.3% of the participants were from a family with 4 people, 35.8% with family member 5, 6.4% with 6 family member, 5.9% and 5% with 3 and more than 6 family members (Table -3). Another study showed 37(64.91%) stayed in extended type of family, 18(31.58%) in nuclear family and 2(3.51%) in 3rd generation family [27]- [30]. 57.2% of the participant's fathers had graduate level, 29.9% higher secondary, 5.3% post graduate, 2.1% primary level and 1.1% illiterate.…”
Section: Resultsmentioning
confidence: 96%
“…Research regarding dark personality traits is limited in the Bangladesh context due to lack of assessment tools for assessing these traits. Roy et al (2010) investigated the association between personality traits, substance abuse, and anti-social behavior and have suggested personality as a determining factor of maladaptive behavior. Therefore, it is crucial to identify the malignant personality traits and its negatively-toned impact on people's adaptive functioning in daily life.…”
Section: Present Studymentioning
confidence: 99%